A Semantical Analysis on Amir Hamzah Poems - Diah Supatmiwati; Heryono Panca Dewantar; Zainuddin Absussamad (LPPM Universitas Bumigora Mataram, 2023)
This study aims to determine the lexical meaning of Amir Hamzah's poem Ibu Dehulu and to identify its referential meaning. In producing a poem, only a few writers like Amir Hamzah produce a poem that contains implied meanings or meanings that are not written down clearly or explicitly through the words written in his poems. Although this poem is an old poem, this poem is contained aesthetic messages and is still interesting and worth reading until now. Based on the explanation and the condition above, the writer is interested in reviewing and analyzing five famous poems by Amir Hamzah through semantic studies. In reviewing the poem, the writer focuses on two types of meaning contained in the semantic field such as lexical meaning, and referential meaning The method used in this research is descriptive qualitative, since the analyzed data were described qualitatively. Qualitative research is a research design that has three formats. The three formats include descriptive, verification, and grounded research formats, then described based on lexical and referential used as a reference for research. The results showed that in the Ibu Dehulu poem by Amir Hamzah selected by the author, there were 5 lexical words that have and referential meanings